A comparison of techniques in age estimation using the third molar. Issue 2 (3rd April 2017) - Berkvens, Michelle E.; Fairgrieve, Scott I.; Keenan, Scott
ABSTRACT: Identification of human remains often depends on estimating the age at death. The most reliable age estimation methods in juveniles have been based on dental development. This study evaluated the Demirjian (DGT), Nolla, and Moorrees, Fanning and Hunt (MFH) methods in estimating age in a modern population from Sudbury, Ontario, Canada using third molars as seen in 361 clinical panoramic digital radiographs of 361 individuals. Inclusion in this study required there to be at least one developing third molar clearly present in the radiograph with a known date of birth. This yielded a sample of 179 females and 182 males with an age range from 7.9 to 29.9 years. All three methods were found to be suitable in the estimation of the chronological age using the third molar. However, the Nolla method proved to be the most applicable at estimating age based on derived polynomial regression R 2 values ranging from 0.854 to 0.891.